DECISIONS IN ECONOMIC-ORGANISATIONAL ENTITIES OPERATING IN A HOSTILE ENVIRONMENT - IOAN CONSTANTIN DIMA; MARIANA MAN (Annals of the University of Petrosani: Economics, 2012)
The complete operating cycle of the organisational economic entity provides a connection between its actions and those actions that take place in the environment where it operates, which are deemed to be natural reactions of the environment to the operation of the organisational economic entity. The way in which the environment reacts to its operation must be understood as being the nature of the relations between events, factors and structures of the environment and not as an answer to what the organisational economic entity does. The same action of the organisational economic entity could therefore determine different environmental reactions to various moments and various actions. This is because organisational economic entities act under the conditions of the restrictions imposed by the environment. There are few cases where these restrictions are not observed and the environment reacts unambiguously. But, most of the time, the operating range is relatively tight, and inside of it only a very low part of it can be assigned to the actions taken by the organisation.